2000
DOI: 10.1159/000020699
|View full text |Cite
|
Sign up to set email alerts
|

Low Leptin mRNA Level in Adipose Tissue and Normoleptinemia in Experimental Chronic Renal Failure

Abstract: Background: Anorexia and weight loss frequently accompany chronic renal failure (CRF). Although multiple metabolic changes occur during CRF, a bulk of evidence indicates that the decrease in caloric intake plays a major role in CRF-induced weight loss. Recently, it has been suggested that elevated plasma leptin concentrations could contribute to anorexia and to downregulation of leptin gene expression in CRF patients. However, in some CRF patients, plasma leptin concentrations have been found to be lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…After electrophoretic fractionation, RNA was transferred overnight to a positively charged nylon membrane (Roche, Mannheim, Germany) by capillary blotting and fixed with UV light. Pre-hybridization and hybridization were performed as described recently [19,22,23].…”
Section: Probes Designing and Labelingmentioning
confidence: 99%
“…After electrophoretic fractionation, RNA was transferred overnight to a positively charged nylon membrane (Roche, Mannheim, Germany) by capillary blotting and fixed with UV light. Pre-hybridization and hybridization were performed as described recently [19,22,23].…”
Section: Probes Designing and Labelingmentioning
confidence: 99%
“…These results suggest that leptin plays an important role in regulation of plasma cholesterol concentration. We found that CRF decreases by about 50 % the leptin gene expression in white adipose tissue from rats [9]. Taking these results as a whole [9,19], one may conclude that an increased rate of cholesterologenesis in CRF rats could partly be a consequence of lower leptin gene expression.…”
Section: Discussionmentioning
confidence: 49%
“…We found that CRF decreases by about 50 % the leptin gene expression in white adipose tissue from rats [9]. Taking these results as a whole [9,19], one may conclude that an increased rate of cholesterologenesis in CRF rats could partly be a consequence of lower leptin gene expression. Slightly lower amounts of food intake by CRF rats cannot be responsible for the increase of HMG-CoA reductase NADPH-producing enzyme gene expression, since fasting or food restriction causes a decrease in these enzymes' activity [8,10,18].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Animals were kept in individual cages with free access to tap water, and with controlled lighting schedule (illuminated from 7 a.m to 7 p.m.). Experimental CRF was induced by two-stage (5/6) subtotal nephrectomy as described previously [ 23 ]. Average daily food intake was measured by the difference in weight between the amount of food provided and the amount remaining over a 1-day period.…”
Section: Methodsmentioning
confidence: 99%